Biomonitoring of cytogenetic effect of antitumor therapy by means of micronucleus assay in exfoliated epithelial cells - Nersesyan, A.K. (Цитология и генетика, 2007)
The data concerning possibility to use micronuclei (MN) level as a biomarker of cytogenetic effects in exfoliated epithelial cells of cancer patients under therapy are presented. The number of MN in buccal cells of cancer patients under chemotherapy are very contradictory. Significant dosedependent increment of MN in tumor and normal epithelial cells due to radiotherapy was shown in most investigations. Evaluation of MN induced by radiotherapy in exfoliated tumor cells can potentially identify radiosensitivity of tumors and the treatment outcome after the first fractions of irradiation. This technique is almost completely non invasive and easily done in accessible primary cancers (oral cavity and uterine cervix). Представлены данные относительно возможности использования теста на микроядра (МЯ) в эксфолиативных эпителиальных клетках онкологических больных, получающих противоопухолевую терапию, как биомаркера цитогенетического эффекта. Количество МЯ у больных, получавших химиотерапию, крайне противоречиво. Почти все исследователи показали, что как в опухолевых, так и в нормальных эпителиальных клетках после радиотерапии число МЯ достоверно увеличивается. Оценка числа МЯ, индуцированных радиотерапией в эксфолиативных эпителиальных клетках, потенциально может выявить радиочувствительность опухоли и эффективность лечения уже после первых сеансов терапии. Этот метод практически неинвазивен и может быть применен в оценке лечения опухолей ротовой полости и шейки матки. Представлено дані відносно можливості використання тесту на мікроядра (МЯ) в ексфоліативних епітеліальних клітинах онкологічних хворих, що отримували протипухлинну терапію, як маркера цитогенетичного ефекту. Кількість МЯ у хворих, що отримували хіміотерапію, дуже суперечлива. Майже всі дослідники показали, що і в пухлинних клітинах, і в нормальних епітеліальних клітинах після радіотерапії число МЯ вірогідно збільшується. Оцінка числа МЯ, що індуковані радіотерапією в ексфоліативно епітеліальних клітинах, потенційно може виявити радіочутливість пухлини та ефективність лікування вже після перших сеансів терапії. Цей метод практично неінвазивний і може бути використаний для оцінки лікування пухлин ротової порожнини та шийки матки.